Indonesian Stratigraphic Lexicon: Past, Present and Future - Darman, Herman; Permana, Asep; Syavitri, Dewi (Ikatan Ahli Geologi Indonesia, 2024)
The Stratigraphic Lexicon is an important source of regional geological information. Due to the development of the science and the geological understanding, the lexicon needs to be updated. Following the first Indonesian Stratigraphic Lexicon by Marks (1957), Harahap et al. (2003) made an update to the lexicon. The latter version was later published online as a website. A GIS format of the lexicon will soon be available for geoscientists to use. This paper also provides suggestions for improving the lexicon, which includes the preparation of logs type for each section. A systematic approach to periodically ever greening the lexicon is necessary. The Geological Survey of Indonesia and the Indonesian Association of Geologists should be involved in the future improvement of the lexicon.